The Influence of Leadership Style, Motivation, and Work Environment, on Environmental Service Employees in Bireuen - Yusuf, M; Mulyadi, Mulyadi; Zalikha, Zalikha; Ariska, Emalia (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study aims to determine the influence of leadership style, motivation, and work environment on the performance of employees of the Environmental Service. This type of research uses Quantitative Research. The data analysis method uses Descriptive Analysis Test, Reliability Test, Validity Test, Classical Assumption Test, and Multiple Linear Regression Analysis. The sample in this study were all employees of the Environmental Service office, totaling 56 employees. the results of the study showed that leadership style, motivation and work environment influenced employee performance both simultaneously and partially.